Use of Executive Orders in Nigeria by the Executive Branch of Government in Time of Emergency - Oluwapelumi Odunayo Osadola; Phebe Oluwatoni Ojo (Britain International for Academic Research (BIAR) Publisher, 2020)
Executive Orders are not invoked as a matter of course by the President or Governors heading the Executive Cabinet. These orders are exercisable when heads of the executive branch of government see for their needfulness and for smooth running of their governmental programmes or policies. Every Executive order must carry the force of law for it to be valid or to be duly recognised by the other branches of government which if not, the latter may question its constitutionality. The advantages of executive orders are very innumerable to mention however it has been said that the use of executive orders have assaulted the concept of separation of powers which is embedded in the 1999 Nigerian Constitution (as amended)as adopted from the United States of America. This paper focuses on the meaning and historical antecedent of executive orders in Nigeria, legal regime or statutory provisions of executive orders in Nigeria, executive orders versus doctrine of separation of power, challenges of executive orders under the 1999 constitution (as amended), praxis of executive orders under the Nigeria fourth republic and lastly is the conclusion and recommendations made thereto. To achieve these, the writers will make use of relevant materials at their disposal.